PENINGKATAN KEMAMPUAN MENULIS PARAGRAF DENGAN MENGGUNAKAN MEDIA CERITA BERGAMBAR PADA SISWA KELAS III DI SDN KOTABARU - Amelia, Nellawati; Suryana, Dudung; Nurani, Riga Zahara (Universitas Pendidikan Muhammadiyah Sorong, 2026)
ABSTRAK: This research is motivated by the low ability of third grade students of SDN Kotabaru in writing paragraphs. The results of the observation showed that only 50% of students achieved the Minimum Completion Criteria (MCC), while the rest had difficulty in constructing sentences logically, choosing the right vocabulary, and understanding paragraph structure. One of the causes is the lack of interesting learning media variations. Therefore, this study aims to improve students' paragraph writing skills by using picture story media. The method used is Classroom Action Research (CAR) model Kemmis and McTaggart which is carried out in two cycles. Each cycle consists of the planning stage, action implementation, observation, and reflection. The subjects of the study were 30 third grade students of SDN Kotabaru. The results of the study showed an increase in every aspect. At the planning stage, the teaching modules and picture story media were arranged completely and relevantly. In the implementation, students were more enthusiastic and actively involved when learning using picture story media. The results of paragraph writing skills also increased. In the pre-action, only 15 students (50%) completed the activity with an average score of 70. In cycle I, it increased to 22 students (73.33%) with an average score of 76.33. In cycle II, completion increased to 27 students (90%) with an average score of 80.16. The conclusion of this study is that the use of picture story media can improve learning planning, student involvement in implementation, and paragraph writing skills of grade III students of SDN Kotabaru. This media has proven effective in helping students understand paragraph structure and develop ideas in writing.